The Effect of Variation of Bar Surface Chamfer Angle on Rotary Friction Welding Connections - Yohanes, Yohanes; Badri, Muftil; Pramija, Syafirman (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
This study aims to determine the effect of chamfer angle variations on flash, welding time, interface and hardness values at welded joints of similar materials. The method was used, with parameters of the rotational speed of 4.335 rpm, friction pressure of 0.5 MPa, forging pressure of 0.7 MPa, forging time of 10 seconds and chamfer angle variations of 0°, 15°, 30°, 45°. Then, the specimen result was tested using the projector profile, Non-Destructive Test (NDT), macro-observation, and Vicker test. The result showed that the greater the chamfer angle variation on the given bar surface, the smaller the size of the resulting flash. The smallest flash dimension was produced at a chamfer angle variation of 45°, with an average flash height of 1.03 mm, successfully reducing the flash height by 62% from variations without chamfer angles. Moreover, an average flash width of 0.26 mm reduced the flash width by 77% of the variation without a chamfer angle. Therefore, the greater the variation of the chamfer angle, the smaller the flash size and the more significant the variation of the chamfer angle, the longer the welding time. In the interface area, chamfer angle variations do not affect cracks and voids. The chamfer angle affects the average hardness value, where the more significant the chamfer angle, the more the hardness value is increased.